The experience of seeking recovery interventions for spinal cord injury during the first year: barriers and facilitators - Anderson, Kim D.; Bryden, Anne M.; Gran, Brian K.; Hinze, Susan W.; Richmond, Mary Ann (Frontiers in Neurology, 2025)
IntroductionSpinal cord injury (SCI) is life changing. Recovery is multi-faceted. Knowing that most injuries are incomplete with potential for meaningful recovery and that there is a limited time during which that recovery occurs, maximizing recovery potential early is essential. The objective of this study was to investigate the experience of newly injured people with SCI and their support persons (SP) while they seek out recovery options during the first-year post injury.MethodsSemi-structured interviews were conducted at three intervals across the first year after having sustained SCI in both Veterans and civilians as well as their SP. Interviews were conducted utilizing an interview guide grounded in two frameworks. Interviews were recorded, transcribed, and deidentified. Codes were developed, revised, or added using a constructivist, grounded theory, analytic approach.ResultsThe main source of recovery options was the inpatient rehabilitation team, with delayed access to research teams and people living with SCI. Insurance and institutions are barriers or facilitators to accessing recovery interventions with clear differences between Veteran and civilian healthcare systems. People and knowledge are facilitators. Interest in clinical trials for recovery grows over time, but there are differences based on race. Finding clinical trials and determining eligibility are significant knowledge barriers to the community.DiscussionThis study has revealed knowledge and power imbalances that significantly impede access to recovery interventions sought by people living with SCI and their support persons during their first year after injury. There are clear differences in the experiences of Veterans and civilians.